Register and Slang: Distinct Forms of Language Variation in Communities - Djamereng, Jumharia; Abdullah, Muhammad Ali Emir (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study investigates the differences between slang and register as forms of language used within communities. Register is language tied to specific groups, interests, or situations. Slang, a part of vocabulary, often reflects age and marks informal communication, particularly among younger generations (Holmes, 2013). This research employed a Systematic Literature Review (SLR) methodology to identify, evaluate, and interpret existing research results. Data were drawn from two studies on slang and register. The research reveals that slang is characterized by trendy, sometimes ungrammatical, vocabulary used primarily by youth in informal settings. Register, while also occasionally deviating from standard grammar, uses vocabulary tied to specific situations and occupations